2011
DOI: 10.1074/jbc.m110.198390
|View full text |Cite
|
Sign up to set email alerts
|

Elevated miR-155 Promotes Inflammation in Cystic Fibrosis by Driving Hyperexpression of Interleukin-8

Abstract: Cystic Fibrosis (CF) is characterized by a massive proinflammatory phenotype in the lung arising from profound expression of inflammatory genes, including interleukin-8 (IL-8). We have previously reported that IL-8 mRNA is stabilized in CF lung epithelial cells, resulting in concomitant hyperexpression of IL-8 protein. However, the mechanistic link between mutations in CFTR and acquisition of the proinflammatory phenotype in the CF airway has remained elusive. We hypothesized that specific microRNAs (miRNAs) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
172
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(182 citation statements)
references
References 58 publications
8
172
0
2
Order By: Relevance
“…Furthermore, the reduction of SHIP by miR-155 activates PI3K/AKT activation [87] . mTOR is a direct target of PI3K/AKT activation, which is activated by AKT phosphorylation.…”
Section: Pi3k/akt Pathwaymentioning
confidence: 99%
“…Furthermore, the reduction of SHIP by miR-155 activates PI3K/AKT activation [87] . mTOR is a direct target of PI3K/AKT activation, which is activated by AKT phosphorylation.…”
Section: Pi3k/akt Pathwaymentioning
confidence: 99%
“…Recent studies have revealed that miR-155 was involved in the development of inflammatory lung disease (20,21). For example, elevated miR-155 could promote inflammation in the lung in cystic fibrosis disease (22). Global miRNA profile analysis showed that the expression of miR-155 was elevated in ALI (21,23).…”
mentioning
confidence: 99%
“…Taken together, these results have indicated the importance of ion channels in the regulation of miRNAs in normal physiological conditions, dysfunction of which may lead to clinical manifestations. Interestingly, by comparing wild type and mutant (DF508)-CFTR lung epithelial cell lines, Bhattacharyya et al [62] recently found that 22 miRNAs were differentially expressed in CFTR defective cells. Among them, the expression of miR-155 was more than 5-fold elevated in CF IB3-1 lung epithelial cells compared with control IB3-1/S9 cells, which was suggested to be responsible for the enhanced expression of IL-8 and exaggerated inflammatory response observed in cystic fibrosis (CF).…”
mentioning
confidence: 99%